Development of a Micro Heat Exchanger Made with Ceramic Multi-Layers (LTCC) and its Setup to Gas Flow Measurements - Vasquez-Alvarez, Elsa; Degasperi, Francisco T. [UNESP]; Gongora-Rubio, Mario R.; Giudici, Reinaldo; deBritoAlves, R. M.; doNascimento, CAO; Biscaia, E. C. (Elsevier B.V., 2009)
A green ceramic tape micro heat exchanger was developed using LTCC technology. The device was designed by using a CAD software and 2D and 3D simulations using a CFD package (COMSOL Multiphysics) to evaluate the fluid behavior in the micro-channels. The micro heat exchanger is composed of five thermal exchange plates in cross flow arrangement and two connecting plates; heat exchanger dimensions are 26 x 26 x 6 mm(3). Preliminary tests were carried out to characterize the device both in atmospheric pressure and in vacuum. The same techniques used in vacuum technology were applied to check the rotameters and to prevent device leakages. Thermal performance of the micro heat exchanger was experimentally tested.
Keywords: LTCC; micro structured heat exchanger; cross flow; simulation